2011
DOI: 10.1037/a0021952
|View full text |Cite
|
Sign up to set email alerts
|

Strain-specific cognitive deficits in adult mice exposed to early life stress.

Abstract: Early life stress is a prominent risk factor for the development of adult psychopathology. Numerous studies have shown that early life stress leads to persistent changes in behavioral and endocrine responses to stress. However, despite recent findings of gene expression changes and structural abnormalities in neurons of the forebrain neocortex, little is known about specific cognitive deficits that can result from early life stress. Here we examined five cognitive functions in two inbred strains of mice, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 33 publications
10
66
0
2
Order By: Relevance
“…In the same way, it is difficult to determine if one sex is more susceptible to MS effects, because the anxiety-25 like behaviour findings were inconsistent. Nonetheless, when comparing BALB/c mice to C57BL/6 mice and other strains, BALB/c appeared to have the most stresssusceptible profile because findings in this strain were less contradictory, suggesting adverse effects in response to MS were higher (Mehta and Schmauss, 2011;Millstein and Holmes, 2007). This also reinforces the hypothesis that BALB/c could be the strain of choice when investigating postnatal manipulation effects.…”
Section: Maternal Separation Effects On Biological and Behavioural Phsupporting
confidence: 78%
See 2 more Smart Citations
“…In the same way, it is difficult to determine if one sex is more susceptible to MS effects, because the anxiety-25 like behaviour findings were inconsistent. Nonetheless, when comparing BALB/c mice to C57BL/6 mice and other strains, BALB/c appeared to have the most stresssusceptible profile because findings in this strain were less contradictory, suggesting adverse effects in response to MS were higher (Mehta and Schmauss, 2011;Millstein and Holmes, 2007). This also reinforces the hypothesis that BALB/c could be the strain of choice when investigating postnatal manipulation effects.…”
Section: Maternal Separation Effects On Biological and Behavioural Phsupporting
confidence: 78%
“…Previous findings indicate that certain mice strains differ in regard to specific behavioural phenotypes and exhibit different responses to environmental challenges and postnatal stressors (Holmes et al, 2005;Kundakovic et al, 2013;Mehta and Schmauss, 2011). C57BL/6 mice, for instance, when compared to BALB/c mice, are more resistant to stress-induced effects early in life (Holmes et al, 2005;Mehta and Schmauss, 2011).…”
Section: Inconsistencies In Ms Studies and Possible Effects On Findingsmentioning
confidence: 97%
See 1 more Smart Citation
“…MATERNAL SEPARATION, RECOGNITION MEMORY AND CADHERIN mRNA 4 Specifically, previous studies have suggested that the BALB/c is one of the most vulnerable mice strain to the MS effects later in life (Mehta & Schmauss, 2011;Millstein & Holmes, 2007;Tractenberg et al, 2016). In this context, daily-prolonged periods of maternal separation (MS) were associated with long-term neurobiological and behavioral consequences (Millstein & Holmes, 2007;Tractenberg et al, 2016;Viola et al, 2016;Wearick-Silva et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…BALB/c mice, but not C57BL/6 mice, have exhibited deficits in spatial working memory and shifts of attention following infant maternal separation. 24 Unpredictable chronic mild stress has induced coat deterioration and decreased grooming behavior in BALB/c mice but not Swiss mice. 25 It is therefore not surprising that BALB/c is usually the strain of choice for studies in which stress plays a central role, such as studies on depression and/or antidepressant effects.…”
Section: Discussionmentioning
confidence: 99%